2007
DOI: 10.1074/jbc.m700088200
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aβ1–11 Antibody Binds to Different β-Amyloid Species, Inhibits Fibril Formation, and Disaggregates Preformed Fibrils but Not the Most Toxic Oligomers

Abstract: Different strategies proposed as therapy for Alzheimer disease (AD) have aimed to reduce the level of toxic forms of A␤ peptide in the brain. Here, we directly analyze the therapeutic utility of the polyclonal anti-A␤ 1-11 antibody induced in 3xTg-AD mice vaccinated with the second generation prototype epitope vaccine. Substoichiometric concentrations of purified anti-A␤ 1-11 antibody prevented aggregation of A␤ 42 and induced disaggregation of preformed A␤ 42 fibrils down to nonfilamentous and nontoxic specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 70 publications
(388 reference statements)
9
97
0
Order By: Relevance
“…Therefore, the level of oligomeric, toxic forms of A␤ is not reduced in the brain of APP Tg 2576 mice at least when vaccination was initiated in mice with pre-existing AD-like pathology. These differences between reducing insoluble and soluble A␤ 42 in vivo are not connected to the differences in binding affinity of anti-A␤ 1-11 antibodies to these forms of ␤-amyloid as we previously demonstrated (Mamikonyan et al, 2007).…”
Section: D-kmentioning
confidence: 80%
“…Therefore, the level of oligomeric, toxic forms of A␤ is not reduced in the brain of APP Tg 2576 mice at least when vaccination was initiated in mice with pre-existing AD-like pathology. These differences between reducing insoluble and soluble A␤ 42 in vivo are not connected to the differences in binding affinity of anti-A␤ 1-11 antibodies to these forms of ␤-amyloid as we previously demonstrated (Mamikonyan et al, 2007).…”
Section: D-kmentioning
confidence: 80%
“…However, given the efficacy of the F(abЈ) 2 fragment alone (55), FcRn may only partially mediate the effects of icv anti-A␤ antibodies. An earlier study precludes another postulated mechanism, namely disaggregation of amyloid, for clearance by 6E10 (61). Rather, it is likely that icv antibodies enter the brain parenchyma and alter a select pool of A␤ species, such as A␤*56 and intraneuronal A␤ (31,36), which in addition to inf luencing cognitive function, may also affect plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…A-Beta peptide (1-42) is toxic to cells and leads to apoptosis and cellular death; previous works performed in vitro and in vivo demonstrated that the oligomeric form of the peptide has the highest toxicity [21]. Here we tested the hypothesis that TTR could protect against this neurotoxicity.…”
Section: Ttr Abolishes A-beta Toxicity In Cell Culturementioning
confidence: 95%